Fluid dynamics of charm quarks in the quark-gluon plasma - Capellino, Federica; Dubla, Andrea; Flörchinger, Stefan; Grossi, Eduardo; Kirchner, Andreas; Masciocchi, Silvia (Physical review, 2023)
A fluid-dynamic approach to charm-quark diffusion in the quark-gluon plasma (QGP) is developed for the first time. Results for integrated yields and momentum distributions of charmed hadrons obtained with a fluid-dynamic description for the dynamics of the QGP coupled to an additional heavy-quark-antiquark current are shown. In addition to the thermodynamic equation of state, this description uses a heavy-quark diffusion constant which we take from lattice QCD calculations. The results describe the experimental data measured at the LHC at the center-of-mass energy of √𝑠NN =5.02 TeV up to 𝑝T∼4-5 GeV/𝑐, showing that charm quarks undergo a very fast hydrodynamization in the medium created by ultrarelativistic heavy-ion collisions.